Comparison of the Reliability of Four Different Movement Thresholds When Evaluating Vertical Jump Performance - Madeleine Barefoot; Hugh Lamont; J. Chadwick Smith (MDPI AG, 2022)
Analyzing vertical jumps performed on a force plate can be useful for the strength and conditioning professional in managing neuromuscular fatigue. The purpose of this study was to compare different movement thresholds when analyzing countermovement (CJ) and squat jump (SJ) performance. Twenty-one college-aged participants (9 female, 12 male) performed five CJs and five SJs. Movement initiation was identified when the vertical ground reaction force (VGRF) deviated five standard deviations (5SD), four standard deviations, (4SD), 2.5% of system weight (2.5%SW), and 10% of system weight (10%SW) from their starting position. For CJs, movement was determined when the VGRF deviated either above or below these thresholds (5SDAB, 4SDAB, 2.5%SWAB, 10%SWAB) and was compared to when VGRF deviated below these thresholds (5SDB, 4SDB, 2.5%SWB, 10%SWB) in terms of peak force (Fmax), net impulse (netIMP), braking impulse (brIMP), propulsive impulse, jump height (JHT), peak power (Pmax), peak velocity (Vmax), and RSImod. For SJs, movement was determined when VGRF initially rose above these thresholds (5SD, 4SD, 2.5%SW, and 10%SW) for Fmax, netIMP, JHT, and Vmax. Significant differences were observed among several methods except for Fmax. However, these differences were small. All CJ measures demonstrated good-to-excellent relative reliability (ICC: 0.790-0.990) except for netIMP for 2.5%SWAB (ICC: 0.479). All methods demonstrated good absolute reliability as measured by percent coefficient of variation (CV%) except brIMP and RSImod. This may be due to instructions given to each jumper as well as skill level. For SJs, no differences in Fmax or netIMP were found across all methods. Small differences were seen for JHT, Pmax, and Vmax across several methods. All methods produced acceptable CV% (<10%) and excellent ICCs (0.900-0.990). However, some jumpers produced CV% that was greater than 10% when determining JHT for 5SD, 4SD, and 2.5%SW methods. This could be due to our method of obtaining system weight. Based on our findings, we recommend using the 10%SW method for assessing SJ performance on a force plate.